A Sustainable Bioeconomy The Green Industrial Revolution - Sillanpää, Mika.; Ncibi, Chaker; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
An authoritative and comprehensive volume of knowledge and green technologies wholly focused on the future of the bioeconomy. The authors present data, show opportunities, discuss R&D findings, analyze strategies, assess the wider economic impact, showcase achievements, criticize policies and propose solutions for the green revolution in biofuels, biochemicals and biomaterials' production and power generation. A fascinating range of case studies from the US, China and many European countries are used to inform readers about the impact of this field on society and how various technologies are currently being implemented. Additionally, the role of industry on this green industrial revolution is outlined with contributions from several major companies such as DuPont (US), UPM-Kymmene Oy (Finland), Anhui BBCA Biochemical Co (China).
Legacy of petroleum economy -- Shifting towards bioeconomy -- Biomass: the key to a sustainable future -- Bioenergy and biofuels -- Biochemicals -- Biomaterials -- Industrial-scale production: Paving the way for bioeconomy -- Implementing the Bioeconomy on the ground -- Bioeconomy: Impact assessment, challenges and solutions -- Exercises and evaluation.
Keywords: Chemistry, Technical; Renewable energy sources; Environmental chemistry; Environmental economics; Sustainability; Industrial Chemistry; Renewable Energy; Environmental Chemistry; Environmental Economics; Sustainability